A Comparative Study of Alcohol Percentage in Homeopathic Mother Tinctures by using GCHS & Conventional Method in Respect to Accuracy and Efficiency (Advancements in Homeopathic Research, 2024)
Introduction: Technological advancement in  homeopathic quality control helps for more accuracy  in data & consumes less time. Technology progression  has led to inclusion of modern instruments like  UV spectroscopy, HPTLC, gas chromatography in  homeopathic quality control. Assessment of alcohol  percentage in homeopathic mother tincture is an  essential quality parameter. However, estimation of  alcohol percentage by using conventional method  (CM) as described in Homeopathic Pharmacopoeia  of India is time consuming at commercial level.  Advanced technology of gas chromatography with  head space (GCHS) is considered to minimise the  process time, improve the efficiency, and provide  more accuracy. However, there is no study to validate  this statement in homeopathic industry. This study is  aimed to find out the difference in both the methods.
Keywords: GCHS; homeopathic mother tincture; alcohol percentage in mother tincture